PENGEMBANGAN MODEL PEMBELAJARAN DAN KARAKTER TERINTEGRASI TIK PADA PROGRAM STUDI EKONOMI ISLAM UIN ALAUDDIN - Andi Zulfikar D; Muslihati Muslihati Muslihati; Azizah Nur Adilah; A. Darussalam Tajang (PROMOSI (Jurnal Pendidikan Ekonomi), 2022)
While times and technology have advanced, some learning methods in education still requirestudents to sit quietly in a closed room (classroom) and listen to the teacher's explanation asthe only source of information, considered irrelevant by some education experts. Severalfactors, such as teaching techniques and ICT-based learning materials, can be taken to createan innovative, comfortable, and enjoyable learning environment. This research is categorizedas a form of development research because the results include creating an ICT-integratedlecture model and an increase in the positive character of students. This study overviews howcharacter education and information technology teaching are integrated. The results showedthat the integration of the model succeeded in integrating the teaching and character educationmodel with ICT, which impacted increasing student learning activities.Keywords: e-Learning Innovation Character Islamic Economic Education